Ten misconceptions about trauma-focused CBT for PTSD. (22nd July 2022) - Murray, Hannah; Grey, Nick; Warnock-Parkes, Emma; Kerr, Alice; Wild, Jennifer; Clark, David M.; Ehlers, Anke
Abstract: Therapist cognitions about trauma-focused psychological therapies can affect our implementation of evidence-based therapies for post-traumatic stress disorder (PTSD), potentially reducing their effectiveness. Based on observations gleaned from teaching and supervising one of these treatments, cognitive therapy for PTSD (CT-PTSD), ten common 'misconceptions' were identified. These included misconceptions about the suitability of the treatment for some types of trauma and/or emotions, the need for stabilisation prior to memory work, the danger of 'retraumatising' patients with memory-focused work, the risks of using memory-focused techniques with patients who dissociate, the remote use of trauma-focused techniques, and the perception of trauma-focused CBT as inflexible. In this article, these misconceptions are analysed in light of existing evidence and guidance is provided on using trauma-focused CT-PTSD with a broad range of presentations. Key learning aims: (1) To recognise common misconceptions about trauma-focused CBT for PTSD and the evidence against them. (2) To widen understanding of the application of cognitive therapy for PTSD (CT-PTSD) to a broad range of presentations. (3) To increase confidence in the formulation-driven, flexible, active and creative delivery of CT-PTSD.